2023
DOI: 10.1136/archdischild-2023-325831
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged use of closed-loop inspired oxygen support in preterm infants: a randomised controlled trial

Tim M R Schouten,
Ameen Abu-Hanna,
Anton H van Kaam
et al.

Abstract: ObjectiveThis randomised study in preterm infants on non-invasive respiratory support investigated the effectiveness of automated oxygen control (A-FiO2) in keeping the oxygen saturation (SpO2) within a target range (TR) during a 28-day period compared with manual titration (M-FiO2).DesignA single-centre randomised control trial.SettingA level III neonatal intensive care unit.PatientsPreterm infants (<28 weeks’ gestation) on non-invasive respiratory support.InterventionsA-FiO2versus M-FiO2control.MethodsMai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…AOC systems consist of an oxygenation monitoring device, (pulse oximeter), gas delivery system (ventilator or cannula), and an algorithm to determine timing and degree of FiO 2 adjustments ( 119 ). Multiple studies, spanning the last 40 years, in term and very low birth weight preterm neonates have demonstrated AOC systems were more effective than manual titration in achieving oxygenation targets ( 120 133 ). There have been some studies that investigated long term effects and found no difference in neurodevelopmental outcome at 2 years of age between the automated oxygen control group and standard of care manual control groups ( 134 ).…”
Section: Methods Of Oxygen Measurement and Titrationmentioning
confidence: 99%
“…AOC systems consist of an oxygenation monitoring device, (pulse oximeter), gas delivery system (ventilator or cannula), and an algorithm to determine timing and degree of FiO 2 adjustments ( 119 ). Multiple studies, spanning the last 40 years, in term and very low birth weight preterm neonates have demonstrated AOC systems were more effective than manual titration in achieving oxygenation targets ( 120 133 ). There have been some studies that investigated long term effects and found no difference in neurodevelopmental outcome at 2 years of age between the automated oxygen control group and standard of care manual control groups ( 134 ).…”
Section: Methods Of Oxygen Measurement and Titrationmentioning
confidence: 99%